Maggie Lindsley papers - Lindsley, Maggie; Lindsley, Maggie
Correspondence, diary, notebook, and other papers relating chiefly to the Civil War. Diary (1864 October 29-1865 May 28) kept by Lindsley concerns the siege of Nashville, Tenn., and life in Washington, D.C., in the final weeks of the Civil War. Lindsley discusses Union generals as well as the attitude of noncombatants. Includes the published version of the diary, Maggie!: Maggie Lindsley's Journal, Nashville, Tennessee, 1864, Washington, D.C., 1865: Including Letters Written to Her in 1862 from Professor Benjamin Silliman of Yale College (1977). Also includes a bound report containing recommendations for the promotion of officers serving under George Henry Thomas; a notebook kept by Lindsley's husband, Robert Hampton Ramsey, while serving as aide to Thomas; and several items removed from the notebook: Special Field Orders #11 (1864 May 22; Kingston) from William T. Sherman, accompanied by a printed map of Cobb County, Ga., and a hand-drawn map. The notebook contains copies of letters pertaining primarily to the Atlanta Campaign, 1864. Letters are chiefly from Thomas to Joseph Hooker, O.O. Howard, John Newton, John McAuley Palmer, William T. Sherman, and Lorenzo Thomas.
Full name: Margaret Lawrence Lindsley Ramsey. Born, circa 1840. Married Capt. Robert H. Ramsey, assistant adjutant general under General George Henry Thomas. Died, 1922.
Collection material in English.
Originally cataloged under Lindsley's full name, Margaret Lawrence Lindsley Ramsey.
Keywords: Hooker, Joseph, -- 1814-1879 -- Correspondence; Howard, O. O. -- 1830-1909 -- Correspondence; Newton, John, -- 1823-1895 -- Correspondence; Palmer, John McAuley, -- 1817-1900 -- Correspondence; Ramsey, Robert Hampton, -- 1838-1876 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Silliman, Benjamin, -- 1779-1864 -- Correspondence; Thomas, George Henry, -- 1816-1870.; Thomas, George Henry, -- 1816-1870 -- Correspondence; Thomas, Lorenzo, -- 1804-1875 -- Correspondence; United States. -- Army -- Officers; Atlanta Campaign, 1864.; Generals -- United States; Nashville, Battle of, Nashville, Tenn., 1864.; Cobb County (Ga.) -- Maps; Georgia -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Washington (D.C.) -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Social life and customs